PROBLEMATIKA PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DAN ALTERNATIF PEMECAHANANNYA - Sholikhah, Octarina Hidayatus (Premiere Educandum, 2015)
In a cooperative learning model, students tasked to construct their own knowledge under the guidance of a teacher who acts as a facilitator and mediator. One model of a cooperative learning is Group Investigation (GI). In its application, found the problem that made the implementation of classroom teaching and learning process is less than optimal. One of the problems that occur are not the evaluation in step group. By reviewing the existing theories and facts that are running in the field, has found a solution to these problems, resulting in improvements in learning steps GI.Â Key word : Problematics, Group Investigation, Troubleshooting